Inter-Creative Course Model Proposal: Teaching-Learning Design in Secondary Schools of TRNC - Ulas Dagli, Ugur; Pasaoglulari Sahin, Nil; Guley, Kamil (Ani Yayincilik, 2013)
Problem Statement: Design is an indispensable part of the human being. It enters one's life on the very first day that the eyes open. Design awareness is developed at an early age. With a proper education, even in the preschool years, design is experienced within one's close environment. Purpose of the Study: This study aims to determine the problems in the design education programs in the secondary schools of North Cyprus through evaluating Design and Technology lessons and proposing solutions in order to enhance the quality of design education. Accordingly, as a result of the first observations, problems occur and are defined, such as a lack of framework, systems, programs, and curriculum in teaching design. Additional problems are observed including a low level of physical and functional quality in the teaching and learning medium. Some teachers have a lack of knowledge and are not capable of teaching design, and some students have a lack of design background. Method: A one-year pilot study was conducted at four different secondary schools of North Cyprus. Accordingly, after the first series of observations were carried out using a random sampling method, the subject matter as the second action was conveyed to the Ministry of Education, which was determined as one of the actors in the action plan. Third, a commission was established by the Ministry of Education in order to initiate the action plan. Fourth, commission members who were selected among experienced experts developed a framework of teaching and learning. Fifth, the developed framework was tested at four pilot schools for a one-year study in addition to feedback given from the Design and Technology teachers in the seminars held. The internal and external feedback reflected the development and revisions to the tested framework. Findings and Results: Inter Creative Course Model was developed in line with the achieved results of the field study and offered three concepts: 1) learning by doing and doing by learning (Hands on minds on,) 2) learning from friends and learning with friends (Over the shoulder learning,) and 3) learning from experience (Know how learning.) The model provided five benefits to the students: increase creative problem solving ability, develop self-confidence, improve social skills, reinforce aesthetic value and develop ability of management. Conclusions and Recommendations: The results of this study indicated that even an intangible concept such as design could easily be taught and learned like a tangible concept such as science or mathematics. A systematic structure including the alphabet of design, which contains its vocabulary and principles, will be presented in this study.
Keywords: design; design education; inter-creative course; learning; teaching; North Cyprus